Impact of thermal and drying regimes, used to make powders derived from spinach leaves, on their material properties and digestibility - Chi, Chao (2024)
Chloroplasts are photosynthetic organelles in plants which are a rich source of lipophilic nutrients like galactolipids, carotenoids, vitamin E and α-linolenic acid (ALA, 18:3). Recent interest in the use of chloroplast fractions as functional food ingredients has led to the development of methods for their isolation from plant tissues. In the current research, the removal of intact chloroplasts from the confinement of the cell wall was achieved using a simple and clean method (slow-screw, twin-gear juicer), without the addition of solvents or chemicals, which is efficient for liberating chloroplasts. This approach was developed in an attempt to avoid excess dilution and contamination as well as maintaining food quality, enhancing shelf-life stability. The extracts were further dried with the use of modern industrial technologies such as spray drying and freeze drying. Thermal preservation technologies such as pasteurisation of spinach juice (70 °C 15s and 90 °C 5min) and blanching of spinach leaves (100°C 30s) were also investigated to inactivate enzymes and eliminate pathogenic microorganisms during storage. Food processing techniques are designed to improve the quality of products, by promoting physical and chemical changes in tissues but can also lead to losses, especially of micronutrients. Thermal processes, such as pasteurisation and blanching, inactivated endogenous enzymes in spinach extracts, with 95%-99% of peroxidase (POD) activity being reduced. The study on drying techniques showed that both spray and freeze drying retained nutrient levels to a similar level in spinach juice powder; and freeze dried chloroplast rich fraction (CRF) had a higher nutritional value than freeze dried juice. In addition, significant reductions in moisture content (below 10%) and water activity (below 0.3) in spinach juice/CRF powders are achieved with this suggesting better microbiological safety and enhanced shelf-life stability. However, thermal processing caused a significant quality loss in terms of colour and nutritional value. Key morphology changes of different treated spinach juice/CRF powders were observed by scanning electron microscopy (SEM) and highlighting the impact of processing procedure on organelle structures and providing a means to differentiate between each method used. In addition, in vitro digestion assays, used to mimic the physiological conditions of human digestion, were used to measure the bioaccessibility of nutrients when spinach juice/CRF were processed in different ways. The digestion model consists of three phases (oral phase, gastric phase and intestinal phase), and the results showed that pasteurisation of spinach juice promoted the bioaccessibility of carotenoids and vitamin E, as well as enhanced the digestibility of galactolipids but hindered proteins digestion in spinach juice/CRF compared with fresh samples. The lipolysis of galactolipids, mainly monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG) was monitored by high performance thin layer chromatography (HPTLC) during digestion. MGDG and DGDG were converted to monogalactosylmonoacylglycerol (MGMG) and digalactosylmonoacylglycerol (DGMG), respectively, and ALA was the main fatty acid released. While the major galactolipid lipolysis occurred during the intestinal phase with the presence of porcine pancreatic extracts (PPE), and the protein hydrolysis occurred mainly during the gastric phase with the addition of pepsin.